The influence of high doses of vitamin C on functional recovery and postoperative pain in patients with trochanteric fracture after intramedullary nailing during a three-month follow-up: a pilot study - Mirza Sivro; Đemil Omerović; Faruk Lazović; Adnan Papović (Medicinski glasnik, 2025)
Aim: To determine the effects of high peri- and postoperative doses of vitamin C administration on severity of pain in postoperative period and functional outcome of the patients with trochanteric fracture treated with intramedullary nailing during a three-month follow-up. Methods: A prospective, randomized, pilot study included 56 patients who were randomly divided into vitamin C (intervention) and control groups. In the intervention group, patients received vitamin C perioperatively by an intravenous route for 2 days, and oral vitamin C for 38 days postoperatively. Baseline characteristics, postoperative metamizole consumption, Visual Analogue Scale (VAS) score, Harris Hip Score (HHS) value, and the prevalence of complications were evaluated in both groups. Results: No significant differences were noted between the groups regarding age, gender, length of hospitalization, and distribution in fracture type. Postoperative metamizole consumption was notably higher in the control group compared to the vitamin C group (p=0.006). Postoperative VAS score was higher in the control group (p<0.05). No significant differences in HHS values were detected between the groups at 6 and 12 weeks postoperatively (p=0.655 and p=0.755, respectively). The group variable significantly contributed to VAS score, and age and gender variables significantly contributed to HHS value. Conclusion: A significant reduction of subjective pain levels and lower analgesic consumption was found in patients who received vitamin C, suggesting that it should be considered as an adjuvant agent for analgesia in patients with hip fracture.
Keywords: analgesics; antioxidants; femur